The myths we live by - Midgley, Mary, 1919-2018 (Routledge, Taylor & Francis Group, 2003)
Mary Midgley argues in her powerful new book that far from being the opposite of science, myth is a central part of it. In brilliant prose, she claims that myths are neither lies nor mere stories but a network of powerful symbols that suggest particular ways of interpreting the world.